2023
DOI: 10.1038/s41593-023-01341-4
|View full text |Cite
|
Sign up to set email alerts
|

Seeding the aggregation of TDP-43 requires post-fibrillization proteolytic cleavage

Abstract: Despite the strong evidence linking the transactive response DNA-binding protein 43 (TDP-43) aggregation to the pathogenesis of frontotemporal lobar degeneration with TDP-43, amyotrophic lateral sclerosis and several neurodegenerative diseases, our knowledge of the sequence and structural determinants of its aggregation and neurotoxicity remains incomplete. Herein, we present a new method for producing recombinant full-length TDP-43 filaments that exhibit sequence and morphological features similar to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…Several studies have suggested that the oligomeric forms of several amyloid proteins play central roles in mediating amyloid toxicity and cell-to-cell propagation of protein aggregates; this process is strongly dependent on their seeding activity, i.e., the ability to induce protein misfolding and fibril formation. Therefore, we next investigated the seeding activity of TDP-43 oligomers. The full-length TDP-43 aggregates and fibrils do not bind to thioflavin T (ThT) because their amyloid core is buried and covered by the RNA-binding domains; thus, we investigated the ability of TDP-43 oligomers to seed the aggregation-prone core peptide corresponding to residues 279–360 as described previously . This TDP-43 fragment forms highly ordered fibrils that bind to ThT, and its aggregation is accelerated by the addition of TDP-43 (279–360) fibrillar seeds (Figure C,D and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have suggested that the oligomeric forms of several amyloid proteins play central roles in mediating amyloid toxicity and cell-to-cell propagation of protein aggregates; this process is strongly dependent on their seeding activity, i.e., the ability to induce protein misfolding and fibril formation. Therefore, we next investigated the seeding activity of TDP-43 oligomers. The full-length TDP-43 aggregates and fibrils do not bind to thioflavin T (ThT) because their amyloid core is buried and covered by the RNA-binding domains; thus, we investigated the ability of TDP-43 oligomers to seed the aggregation-prone core peptide corresponding to residues 279–360 as described previously . This TDP-43 fragment forms highly ordered fibrils that bind to ThT, and its aggregation is accelerated by the addition of TDP-43 (279–360) fibrillar seeds (Figure C,D and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal His-SUMO fusion protein was prepared following a protocol previously developed in our laboratory. 40 Briefly, the plasmid was transformed and overexpressed in E. coli strain BER2566. A 3 L bacterial culture was harvested at 4000 rpm for 15 min at 4 °C.…”
Section: ■ Methodsmentioning
confidence: 99%
See 3 more Smart Citations